Menganalisis Manajemen Kelas oleh Guru di SMA Swasta Utama Medan di Kecamatan Medan Tembung Kota Medan - Lusia Oktaviani; Maria Dwi Sianipar; Qamara Aulia Ananada; Sanas Tasia; Asima Pasaribu; Ade Fransiska (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Classroom management skills are one of the fundamental competencies in teaching aimed at creating and maintaining an optimal learning environment. In other words, this skill is closely related to the professional abilities of teachers to produce favorable conditions, provide enjoyment for learners, and foster a healthy learning discipline. This study aims to understand how classroom management is implemented at Private High School Utama Medan located in Medan Tembung District, Medan City. The method used in this research is qualitative descriptive. Several issues that arise in classroom management at Private High School Utama Medan include: students seeking attention, emotional students, students facing learning difficulties, students who struggle to cooperate with their group mates, groups that violate regulations, a lack of adequate learning media, and a classroom atmosphere that is not supportive.